Strategy for Developing Flower Potential in Musuk District, Boyolali Regency - Siwi Istiana Dinarti; Yuslinawari Yuslinawari; Putri Nawang Astari; Aulia Afifah; Kusnadi Jhon Pranata Napitupulu (Journal of Agriculture, 2026)
The rose flower, as a commodity widely cultivated in Musuk District, possesses great potential to boost both regional and local economies. Despite the significant potential of rose flowers, it has not yet been optimized by the community and government. The lack of community knowledge regarding the existing potential is one of the factors contributing to the suboptimal production of these rose flowers. The aim of this research is to identify the potential of rose flowers and analyze strategies for developing the existing rose flower potential in Musuk District. The method used in this research is a descriptive qualitative approach. Informant selection technique utilized snowball sampling. SWOT analysis was the analytical method employed to determine the condition of the rose flower potential and to formulate strategies for its development and economic improvement. The SWOT analysis results indicate that the rose flower potential is in Quadrant V, suggesting that the rose flower is in a stable condition but lacks a strong competitive advantage. Strategies to optimize the rose flower potential include diversifying rose flower products, expanding the market, and conducting replanting to rejuvenate old rose plants to increase production. Efforts to enhance the economy through rose flower potential involve product diversification into items like rose chips, rose tea, rose syrup, and rose water.